A System Design for Distributed Energy Generation in Low-Temperature District Heating (LTDH) Networks. Issue 1 (4th February 2019) - Jones, Sean Rhys; Gillott, Mark; Boukhanouf, Rabah; Walker, Gavin; Tunzi, Michele; Tetlow, David; Rodrigues, Lucelia; Sumner, Mark
Project SCENIC (Smart Controlled Energy Networks Integrated in Communities) involves connecting properties at the University of Nottingham's Creative Energy Homes site in a community scale, integrated heat and power network. The system will use distributed generation to develop the prosumer concept, where consumers are both buyers and sellers of energy in both heat and power systems. The first of its kind, the system consisting of a network flow loop to supply heat to homes, and a generation loop to collect energy from residential heating systems and supply it to a thermal store. To achieve the design, steady state heat load and dynamic building modelling have been used. A pre-insulated pipe was sized using flow rate calculations. The diameter ranges from 40 to 25 mm, with a heat loss as low as 7.0 W/m. In addition, flow rates will fluctuate below a maximum of 1.99 l/s. A standard heat interface units (HIU) has been selected as the network-building link, to satisfy a calculated peak design heating loads of between 36.74 and 44.06 kW. Furthermore, to enable the prosumer concept and associated business models an adapted HIU was selected to interface the distributed heat sources with the network. This paper gives details of the concept, energy flows, calculated and modelled results for the heat network. A premise is given to maintaining low temperatures in the network to ensure system efficiency in line with the latest research thinking.